Pendampingan dan Pembuatan Pupuk Organik "Jakaba" untuk Petani di Dusun Sumbersari, Desa Tulusbesar, Kecamatan Tumpang, Kabupaten Malang - Ety Saraswati; Agus Widarko; Achmad Agus Priyono (Jurnal Abdimas Indonesia, 2025)
The Jakaba organic fertilizer program, implemented in Dusun Sumbersari, Desa Tulusbesar, Malang, Indonesia, addresses the challenges faced by local farmers due to their reliance on expensive and increasingly scarce inorganic fertilizers. The program leverages readily available resources, using rice wash water, molasses, and EM4 to create a cost-effective organic liquid fertilizer (Jakaba). Laboratory tests suggest a potential 20% increase in crop productivity. Fifteen farmers participated in a hands-on training program combining theoretical instruction on sustainable agriculture and practical workshops on Jakaba production and application. All participants successfully learned to produce Jakaba, demonstrating the program's effectiveness in transferring skills. A cooperative farming group was also established to foster collaboration and resource sharing. While some farmers initially combined Jakaba with inorganic fertilizers, the program shows promise, with ongoing monitoring planned to assess long-term impacts on productivity and environmental sustainability. The low production cost of Jakaba (estimated at Rp 500-1000 per liter) makes it an economically viable alternative for local farmers, promoting agricultural resilience and environmental conservation.